HUBUNGAN TINGKAT PENGETAHUAN PASIEN PENDERITA HIPERTENSI TERHADAP SIKAP DALAM PENCEGAHAN STROKE - Larasati Inayah; Safri Safri; Arneliwati Arneliwati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The prevalence of hypertension in Indonesia reaches 25.8 of the population at the age of  over 18 years. Knowledge andattitude awareness to prevent stroke complication need to be done by hypertension sufferers because they  to beaffilicted to stroke. This study aimed to identify the correlation of knowledge of patients with hypertension to anattitudes in preventing stroke in poly internal medicine of RSUD Arifin Achmad Riau Province. This research usesdescriptive correlational research design. The number of samples was 40 people. Information and data were obtained byusing questioner. The results of the research showed that 30% of the patient's knowledge has been categorized into goodand 62.5% attitude in preventing stroke has also already been in the good category. The analysis of correlation betweenknowledge of  patient with hypertension to the attitude in preventing stroke was measured by using Chi Square p value= 0,02 (<α 0,05). The conclusion indicates that  there is an analysis of the relationship of patients knowledge ofhypertension to the attitude in the preventing stroke. It is suggested to the next researcher to do research on factors thatinfluence attitude of patient's with hypertension in preventing stroke.Keywords: Hypertension, Knowledge, Stroke Prevention